(untitled) (Experimental biology, 2015)
Chronic exposure to cadmium chloride leads to a significant violation of the structural integrity of the gum tissue, an increase of intercellular space and decrease the bulk density desmosomalnyh contacts, expansion of interstitium, reducing the intensity of the blood-tissue exchange, which causes inhibition of transport of lymph from the gums.